2010
DOI: 10.1590/s1809-29502010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da reeducação postural global no alinhamento corporal e nas condições clínicas de indivíduos com disfunção temporomandibular associada a desvios posturais

Abstract: Este estudo visou verificar o efeito da técnica de reeducação postural global (RPG) nas condições físicas, psicológicas e psicossociais, assim como no alinhamento corporal, de indivíduos com disfunção temporomandibular (DTM) associada a desvio postural. Participaram 20 indivíduos com DTM e com desvio postural confirmado por exame físico, avaliados, antes e depois do tratamento de RPG, pelos critérios diagnósticos de desordens temporomandibulares (RDC/TMD, na sigla em inglês) e quanto às medidas angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
0
11
0
5
Order By: Relevance
“…Descritores | fisioterapia; postura; amplitude de movimento articular; terapia por exercício.. ucation performed on the ground, indicating that the effects of exercises performed while lying down may be transferred to the standing posture 8,9 . It was indeed verified that Pilates generated gain in the flexibility and muscle strength of ballet dancers 10 .…”
mentioning
confidence: 99%
“…Descritores | fisioterapia; postura; amplitude de movimento articular; terapia por exercício.. ucation performed on the ground, indicating that the effects of exercises performed while lying down may be transferred to the standing posture 8,9 . It was indeed verified that Pilates generated gain in the flexibility and muscle strength of ballet dancers 10 .…”
mentioning
confidence: 99%
“…Due to the close relation between the muscles of the head and the cervical region with the stomatognathic system, postural deviations can occur in the head and body (SUN et al, 2015;RUSSELL, CONNOR, 2014;BASSO, CORRÊA, SILVA et al, 2010). Therefore, the radiotherapy performed in this region may, in some way, in addition to causing fibrosis and decreased functionality in the temporomandibular joint and masticatory muscles, also be related to important functional alterations in body structures that were not directly affected by the radiotherapy, such as cervical region, shoulder, scapular girdle and upper limbs, which explains the results of this study, where many participants showed loss of function not only in the irradiated regions, but also in regions that were not the focus of the radiation, such as trapezius 64 (90.1%) and pectoralis 57 (80.3%).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that postural deviations generate tension in muscle chains, and result in the masticator and neck muscles 28,30 , being able to influence the function of the larynx.…”
Section: Researchmentioning
confidence: 97%